2010
DOI: 10.3390/molecules15107313
|View full text |Cite
|
Sign up to set email alerts
|

Plant Phenolics: Extraction, Analysis and Their Antioxidant and Anticancer Properties

Abstract: Phenolics are broadly distributed in the plant kingdom and are the most abundant secondary metabolites of plants. Plant polyphenols have drawn increasing attention due to their potent antioxidant properties and their marked effects in the prevention of various oxidative stress associated diseases such as cancer. In the last few years, the identification and development of phenolic compounds or extracts from different plants has become a major area of health- and medical-related research. This review provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

54
2,277
1
106

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 3,386 publications
(2,438 citation statements)
references
References 254 publications
(297 reference statements)
54
2,277
1
106
Order By: Relevance
“…However antioxidant capabilities and anti-cancer abilities did not correlate well. Antioxidants are known to act as pro-oxidants and inhibit cell viability via Fenton reaction (Dai and Mumper 2010) exhibiting anti-cancer properties. In our study extracts with (Murugan and Iyer 2013;Guner et al 2015), there are others claiming a protective role for those substances as cancer cells are known to require antioxidants for their survival Lee et al 2013;Mezghani et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However antioxidant capabilities and anti-cancer abilities did not correlate well. Antioxidants are known to act as pro-oxidants and inhibit cell viability via Fenton reaction (Dai and Mumper 2010) exhibiting anti-cancer properties. In our study extracts with (Murugan and Iyer 2013;Guner et al 2015), there are others claiming a protective role for those substances as cancer cells are known to require antioxidants for their survival Lee et al 2013;Mezghani et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo evidence has pointed out that phytochemicals affect a broad range of intracellular molecular targets. [3][4][5][6][7] In particular, polyphenols may exert anticancer effects by several mechanisms such as reducing the pro-oxidative effect of carcinogenic agents, 8,9 modulation of cancer cell signaling, 10,11 cell cycle progression, 12,13 promotion of apoptosis, 14,15 and modulation of enzymatic activities. 16 Regarding prostate cancer progression, a recent clinical trial assessed the effect of a polyphenol-blend dietary supplement over prostate-specific antigen (PSA) levels in men with localized prostate carcinoma; this study found a significant favorable effect on the percentage rise in PSA levels, an important indicator of prostate cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the dominant secondary metabolites in the fractions is (Marcia et al, 2011;Hussein et al, 2013). The effectiveness of flavonoid in retarding lipid oxidation in fat containing foods is related to their ability to act as free radical acceptors (Dai and Mumper, 2010) or as chelators of metal ions. The chelation by flavonoids is due to ortho-dihydroxy (3, 4-dihydroxyl) group on the β-ring in their chemical structure (Dai and Mumper, 2010).…”
Section: Resultsmentioning
confidence: 99%